1996
DOI: 10.1016/0029-7844(96)00024-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of external peer review on cesarean delivery rates: A statewide program

Abstract: This joint-specialty society and health department peer review had no apparent impact on cesarean rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…32 Nine of the 11 studies evaluating audit and feedback demonstrated a positive impact on guideline implementation. 18,38,40 -46 One study presented mixed effects 26 because of the contamination of the control group by a national effort to promote vaginal birth after cesarean delivery and the weakness of feedback quality. Most of the studies concerned labor management and medical interventions in peripartum care, particularly cesarean procedures.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…32 Nine of the 11 studies evaluating audit and feedback demonstrated a positive impact on guideline implementation. 18,38,40 -46 One study presented mixed effects 26 because of the contamination of the control group by a national effort to promote vaginal birth after cesarean delivery and the weakness of feedback quality. Most of the studies concerned labor management and medical interventions in peripartum care, particularly cesarean procedures.…”
Section: Resultsmentioning
confidence: 96%
“…18,29,34 -36,39,50,52 The remaining studies were rated "fair." The main reasons for the fair quality rating for randomized controlled trials and controlled before-after studies were that protection against exclusion bias was not clear, 24,27,30,38 baseline measures were not reported or were unclear, 26,27,32,33,37 reliable primary outcome measures were unclear or not reported, 24,28,30,37,38 and protection against contamination was not clear. 28,37 Twelve interrupted time series studies were rated "fair" because no autoregressive integrated moving average models (ARIMA) or time series regression models were used for data analysis.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…29 Peer review has been tried in efforts to lower the cesarean delivery rate with variable success, although not in our institution. 3032 …”
Section: Commentmentioning
confidence: 99%